(untitled) (Research, Society and Development, 2021)
This article aims to describe the experiences of the “Training Course for Food Handlers at Municipal Schools in Fortaleza” and to assess the impact on the acquisition of knowledge about Food and Nutrition (NA) and Good Handling Practices (BPM). This work has a qualitative and quantitative approach for a better interpretation of the repercussions related to the training. The course was offered to 600 professionals from 527 institutions linked to the National School Feeding Program, with students from the State University of Ceará, in partnership with nutritionists from the School Feeding Cell of the Municipal Department of Education, as facilitators of the activities. On the first and last day of the course, a questionnaire was applied to assess the participants’ level of knowledge in AN and BPM. Among the 28 items of this questionnaire, there was a statistically significant difference in the correct answers of 20 items (71.42%), 11 (73.3%) of the AN theme and 9 (69.2%) of BPM. The increase in the percentage of correct answers after training suggests an increase in the level of knowledge of food handlers. With the carrying out of activities, focusing on more playful and integrative strategies to favor the learning process, the satisfaction and engagement of participants was perceived when sharing their experiences and practices. As a University Extension activity, the completion of the Course provided benefits to undergraduates, nutritionists and civil society.